Effectiveness of community health education program in improving handwashing with soap behavior among school-age children - Universitas Nurul Hasanah Kutacane, Siska Putri; Mahendika, Devin; Tawil, Muhammad Risal; Ningsih, Warti; Rahagia, Rasi (Institute Of Computer Science (IOCS), 2025)
Handwashing with soap behavior in school-age children is still a serious concern in efforts to prevent infectious diseases. This study aimed to assess the effectiveness of a community-based health education program in improving handwashing with soap behavior among elementary school students. The study used a quasi-experimental design with a pre-test and post-test approach on 150 students from three schools in rural areas. Data were collected through questionnaires and direct observation, then analyzed using descriptive and inferential statistics. The results showed a significant increase in knowledge (from 58.4 to 82.7) and frequency of HWWS behavior (from 40% to 85%) after the intervention. Inferential analysis also showed that age and location factors interacted with the effectiveness of the intervention. The implications of this study suggest that a community-based health education approach is an effective and sustainable strategy in promoting hygienic behavior in schools, and can be adapted for public health programs in other areas.